An observational study of serum vitamin D levels in pregnancy complicated with spontaneous preterm birth. - Dahlia Abd Malik; Mohamad Nasir Shafiee; Mohd Hashim Omar; Nor Azlin Mohamed Ismail; Dian Nasriana (Department of Surgery, UKM Medical Centre, 2014)
This observational study was conducted in the Department of Obstetric and Gynaecology, Universiti Kebangsaan Malaysia Medical Centre. The eligible women were grouped into 3 arms after assessment of antenatal history, vitamin D level and bacterial vaginosis status. Women who continued their pregnancy till term were allocated as the control arm, whereas the preterm arm was further divided into pregnancies continued until term and those who delivered prematurely. The pregnancy and the neonatal outcomes were measured.